Urothelial carcinoma of urinary bladder with exclusive heterologous component of epithelioid rhabdomyosarcoma at metastatic site - Poojan Agarwal; Sunil Pasricha; Gurudutt Gupta; Anila Sharma; Anurag Mehta (Wolters Kluwer Medknow Publications, 2018)
Urothelial carcinoma of urinary bladder with divergent differentiation into rhabdomyosarcoma (RMS) is an extremely uncommon aggressive phenomenon. We present a case of a 74-year-old male with bladder carcinoma which metastasized to the abdominal wall as epithelioid RMS. To the best knowledge of our literature searches, an oligometastasis of exclusive heterologous component has not been described before. The clinical, radiological, and immunohistochemistry profile of the patient supported the monoclonal nature of the tumor.